Architecture now 5! - Jodidio, Philip, 1954- (Köln : Taschen, 2007)
Now in its fifth installment, the Architecture Now! series is an ongoing project documenting the work of the most innovative and influential architects across the globe. Volume 5 features famous names and newcomers alike, and this time around a number of designers are also included, reflecting the new ways in which design and architecture are coming together. Since architecture also extends beyond walls, landscape architecture makes its appearance as well. Easy-to-navigate illustrated A-Z entries include current and recent projects, biographies, contact information, and web sites.Featured architects: Marcos Acayaba, Emilio Ambasz, Tadao Ando, Ron Arad, Asymptote, Atelier SoA, Atelier Tekuto, Cecil Balmond, Cecil Balmond/Rem Koolhaas, Böge Lindner Architekten, Bohlin Cywinski Jackson, Aldo Celoria, Doug Chiang, David Chipperfield, Matali Crasset, Curiosity, Devanthéry & Lamunière, Diller Scofidio + Renfro, Evan Douglis Studio, Elmgreen & Dragset, Antón García-Abril, Mario Garzaniti, Frank O. Gehry, Sean Godsell, Graft, Zaha Hadid, Steven Harris, Hertl, Herzog & de Meuron, HHF architects, HOLODECK.at, Toyo Ito, Jarmund/Vigsnæs, Patrick Jouin, Jesse Judd, Anish Kapoor, Bernard Khoury, Marcio Kogan, Localarchitecture, Guilherme Machado Vaz, MacKay-Lyons Sweetapple, Meixner-Schlüter-Wendt, Paulo Mendes da Rocha, Menis Arquitectos/AMP Arquitectos, Toshiko Mori, Morphosis, Neutelings Riedijk, Oscar Niemeyer, Ryue Nishizawa, NO.MAD Arquitectos, osa - office for subversive architecture, John Pawson, Peanutz Architekten, Arsenio Pérez Amaral, Pezo von Ellrichshausen, Renzo Piano, Pivnice LTD, Pornchai Boonsom, Muti Randolph, Richard Rogers, Stanley Saitowitz, SANAA, Sanaksenaho Architects, Álvaro Siza, Spillmann. Echsle Architekten, Philippe Starck, Ross Stevens, Philippe Stuebi, Hiroshi Sugimoto, SYSTEMarchitects, UNStudio, Wandel Hoefer Lorch + Hirsch, White, Makoto Yokomizo
Keywords: Architectuur -- Geschiedenis -- 20ste eeuw; Architectuur -- 1990-.